REFORMASI BIROKRASI PELAYANAN PUBLIK DI BADAN PELAYANAN PERIJINAN TERPADU (BPPT) KOTA SEMARANG DALAM MENCAPAI PELAYANAN PRIMA - Sari, Erlina Widian; Widowati, Nina (Journal of Public Policy and Management Review, 2016)
Bureaucratic reform is basically an effort to perform renewing and fundamental changes, systematic and thorough in system of government. This research aims to understand the implementation of bureaucratic reform public services in achieving excellent service and know aspects that inhibits in the implementation of bureaucracy reform in BPPT Semarang. This research uses method qualitative study. The result of this research is implementation of the bureaucracy reform in BPPT has shown excellent service and service provided by BPPT had already demonstrated excellent service, there are still some aspects need to be improved. Aspects that needs to be repaired it can be seen of the dimensions of prime service consisting of simplicity; clearness; certainty time; accuracy; security; responsibility; completeness facilities and infrastructure, accessibility; discipline, civility and cordiality; and comfort. Aspects that needs to be repaired among others certainty time, completeness facilities and infrastructure, accessibility, and discipline. BPPT Semarang must always seeks to provide excellent services according to the development of technology and society`s need, providing a means of infrastructures supporting for services, and socialization information to the community through use of portal website